2017
DOI: 10.12688/wellcomeopenres.10784.1
|View full text |Cite
|
Sign up to set email alerts
|

Micro-epidemiological structuring of Plasmodium falciparum parasite populations in regions with varying transmission intensities in Africa.

Abstract: Background: The first models of malaria transmission assumed a completely mixed and homogeneous population of parasites.  Recent models include spatial heterogeneity and variably mixed populations. However, there are few empiric estimates of parasite mixing with which to parametize such models. Methods: Here we genotype 276 single nucleotide polymorphisms (SNPs) in 5199 P. falciparum isolates from two Kenyan sites and one Gambian site to determine the spatio-temporal extent of parasite mixing, and use Principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 67 publications
3
45
2
Order By: Relevance
“…In order to predict whether targeting hotspots is potentially an effective way of interrupting transmission, we need to understand the spatial and temporal scales over which parasite mixing can be observed. Limited genetic differentiation between malaria parasites has been shown to occur on a regional scale in sub-Saharan Africa 1820 , although we previously identified spatial structure at fine micro epidemiological scales within geographically defined regions in Kenya and The Gambia 21 .…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…In order to predict whether targeting hotspots is potentially an effective way of interrupting transmission, we need to understand the spatial and temporal scales over which parasite mixing can be observed. Limited genetic differentiation between malaria parasites has been shown to occur on a regional scale in sub-Saharan Africa 1820 , although we previously identified spatial structure at fine micro epidemiological scales within geographically defined regions in Kenya and The Gambia 21 .…”
Section: Introductionmentioning
confidence: 63%
“…<10km), despite a high level of parasite mixing 21 . In the present analysis, we examined the level of parasite mixing at a sub-national scale in Western Kenya, using parasitological data from primary school surveys to describe the patterns of parasite mixing at a larger geographical scale.…”
Section: Discussionmentioning
confidence: 97%
“…Such studies are usually conducted at countrywide spatial scales, aiming to identify provinces or districts where malaria control could be scaled up towards elimination [36]. On the other hand, assuming that parasites spread from transmission foci to surrounding areas, clusters of genetically similar parasites are identified (Figure 1B), expecting that control efforts targeting foci may also have beneficial effects on surrounding areas [37]. The spatial scale of such studies is usually smaller.…”
Section: Assessing Population Structure To Inform and Guide Malaria Cmentioning
confidence: 99%
“…Owing to these requirements, relatively few studies have been conducted. In Ghana, Kenya, Solomon Islands, and the Peruvian Amazon, relatedness of parasites collected across a range of a few km was found, suggesting gene flow at small scales but limited parasite migrations at larger scales [37, 42, 43]. It remains to be shown under what conditions, and at what geographical scale, transmission foci can be identified that are stable over time and thus could be targeted for malaria control.…”
Section: Assessing Population Structure To Inform and Guide Malaria Cmentioning
confidence: 99%
See 1 more Smart Citation